2011
DOI: 10.1136/bmj.d6128
|View full text |Cite
|
Sign up to set email alerts
|

Honorary and ghost authorship in high impact biomedical journals: a cross sectional survey

Abstract: Objectives To assess the prevalence of honorary and ghost authors in six leading general medical journals in 2008 and compare this with the prevalence reported by authors of articles published in 1996.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
268
4
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(292 citation statements)
references
References 16 publications
5
268
4
15
Order By: Relevance
“…However, we are wary about how comparable this study is with the others cited by the authors. [2][3][4] Roper and Korenstein open their article by defining guest authorship as Battribution of research article authorship to investigators not meeting standard authorship criteria,^yet fail to use standard authorship criteria in their study. They also suggest their guest authorship criteria are conservative and may underestimate the true prevalence of guest authorship.…”
Section: T O the Editorsmentioning
confidence: 99%
“…However, we are wary about how comparable this study is with the others cited by the authors. [2][3][4] Roper and Korenstein open their article by defining guest authorship as Battribution of research article authorship to investigators not meeting standard authorship criteria,^yet fail to use standard authorship criteria in their study. They also suggest their guest authorship criteria are conservative and may underestimate the true prevalence of guest authorship.…”
Section: T O the Editorsmentioning
confidence: 99%
“…Responses showed that 12% of research articles published in 2008 had one or more ghost authors, and 25% of the research articles had one or more honorary authors. 1 These percentages would likely be higher if the study was generalized to different types of journals with a more diverse author pool in terms of discipline and country of origin than those of these six journals that have used the same criteria for authors for many years.…”
Section: Me First Me Equallymentioning
confidence: 99%
“…2,5,12,17,23 Analysis performed on a sample of authors of 896 articles published in leading medical journals (Annals of Internal Medicine, JAMA, Lancet, Nature Medicine, New England Journal of Medicine and PLoS Medicine) showed a reasonable proportion (17.6%) of cases in which individuals who were included as authors had not contributed suffi ciently to merit this designation, characterizing the so-called "honorary authorship". Considering only research articles, this proportion reached 25%.…”
Section: Introductionmentioning
confidence: 99%